Change of Financial Behavior Paradigm of the Stock Market Subjects - MALYSHENKO, K. A.; MALYSHENKO, V. A.; PONOMAREVA, E. Y.; ANASHKINA, M. V. (Journal of Advanced Research in Law and Economics; Vol 9 No 2 (2018): JARLE Volume IX Issue 2(32) Spring 2018, 2018)
The article is devoted to the evaluation of irrational investor behavior in the stock market, a situation in which investors take irrational decisions and factors influencing these decisions. Analyzes the works of foreign authors and theories describing the reactions and the behavior of the stock market and trade. Emphasizes the stages of formation of the ‘Efficient Markets Hypothesis’ as the basis for the formation of the linear paradigm. Examines the emergence and development of non-linear paradigm. Also, study proposes a new paradigm in the financial behavior of market participants – the logistics paradigm, as a further development of the nonlinear paradigm, which substantiates not only over - and under - reaction of the market but multidirectional orientation of the reactions of the market and of the impact of fundamental news also. For this purpose, the study uses an original method – elasticity of information, as the reaction measure of the stock market to certain news of all the society.